2004
DOI: 10.2105/ajph.94.7.1230
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Smoking and Exposure to Tobacco Marketing Under a Tobacco Advertising Ban: Findings From 2 Norwegian National Samples

Abstract: Adolescents' current smoking and future smoking expectations are linked to marketing exposure even in limited settings, suggesting the need for comprehensive controls to eliminate the function of marketing in promoting adolescent smoking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
0
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 49 publications
(33 reference statements)
4
28
0
2
Order By: Relevance
“…Also, many of them believed that cigarettes are easily accessible to youth within their community. We also observed that more respondents who had been sent on such errands reported that they were likely to initiate cigarette smoking within the coming year and this is in agreement with other studies where reducing access has been recommended to curb smoking susceptibility [25][26][27] . In a country like Nigeria, where many youth are never-smokers,6 sending under-aged youth to purchase cigarette increases their accessibility to cigarettes and might play a factor in cigarette experimentation and initiation 24 .…”
Section: Discussionsupporting
confidence: 91%
“…Also, many of them believed that cigarettes are easily accessible to youth within their community. We also observed that more respondents who had been sent on such errands reported that they were likely to initiate cigarette smoking within the coming year and this is in agreement with other studies where reducing access has been recommended to curb smoking susceptibility [25][26][27] . In a country like Nigeria, where many youth are never-smokers,6 sending under-aged youth to purchase cigarette increases their accessibility to cigarettes and might play a factor in cigarette experimentation and initiation 24 .…”
Section: Discussionsupporting
confidence: 91%
“…La publicidad juega un papel crucial en el consumo de cigarrillo, pues está orientada principalmente a la población adolescente y aumenta el inicio y la persistencia del consumo (45). Estos resultados sugieren que el consumo diario de cigarrillo se establece en la adolescencia temprana, lo que implica que el consumo de cigarrillo no es una conducta pasajera en un número importante de adolescentes.…”
Section: Discussionunclassified
“…26 Two decades after Norway banned advertising in traditional media, adolescents' (ages 13–15) self-reported exposure indicated market penetration in multiple channels, particularly branded promotional items and point of sale. 27 The persistent association of exposure and intention to smoke under legislated bans suggests that even limited exposure among adolescents remains a cause for concern. 2527 …”
Section: Promotionmentioning
confidence: 99%